Family and psychological health of the primary caregiver of dependent elderly - Aida Isabel Jordán-Bolaños; Melvin José Zavala-Plaza; Patricio Aníbal Bedoya-Vaca; Cristina Elizabeth Rodríguez-Chicaiza; Sergio Teodomiro Barreno-Sánchez (Revista Información Científica, 2021)
Introduction: knowledge of the socio-familiar influences on caregivers of the elderly is necessary to help establish the degree of family functionality and the psychological pattern (alterations) of the caregiver.